STRATEGI BERSAING PT. PERTAMINA DRILLING SERVICES INDONESIA DALAM INDUSTRI HULU MIGAS INDONESIA - , Wahyu Wibowo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Continuously changing business environment requires companies to steadily adapt and respond quickly in order to maintain their survival or competitiveness in an industry. These changes are also conducted by companies engaged in upstream oil and gas drilling services. When a number of companies begin to appear along with the growth rate of market supply and services as well as better quality, then competition in the industry becomes increasingly competitive. To be able to manage their growth and sustainability, companies need to have an effective competitive strategy to respond changing business environment. The objective of this research is to identify the both external and internal factors as well as analyzing the competitive strategy that is appropriate for PT. Pertamina Drilling Services Indonesia (PT. PDSI) based on those related factors. To be able to find out how well does the company respond to external factors, an analytical tool in the form of an External Strategic Factors Analysis Summary matrix (EFAS) was used, while to see the internal position of the company, an analytical tools in the form of an Internal Strategic Factors Analysis Summary matrix (IFAS) was applied. Identification and mapping of the strategic position of the main competitor to the PT. PDSI was also conducted by using competitive profile matrix. Based on the analysis of external and internal factors, obtained strengths, weaknesses, opportunities, and threats of PT. PDSI was obtained. By using analytical tools namely Internal-External matrix (IE matrix) as well as a SWOT analysis using SWOT matrix, the company's position and alternative strategies that are appropriate for PT. PDSI were obtained. The results showed that the position of PT. PDSI based on IE matrix is located on the fifth cell namely hold and maintenance position. The appropriate strategies in this position are market penetration and market development. In order to realize the vision of the company to a drilling services provider with international reputation, there is alternative strategy that might be added to the sustainability and growth of the company's business namely market development strategy. Furthermore, by using SWOT matrix, it could be identified some alternative appropriate strategies by combining the strengths, weaknesses, opportunities, and threats, there for it could be formulated S-O (Strengths-Opportunities), S-T (Strengths-Threats), W-O (Weaknesses-Opportunities), and W-T (Weaknesses-Threats) strategies.